The blood brain barrier: Insights from development and ageing. Issue 4 (2nd October 2017) - Delaney, Conor; Campbell, Matthew
ABSTRACT: The blood brain barrier is a necessity for cerebral homeostasis and response to environmental insult, thus loss in functionality with age creates opportunities for disease to arise in the aged brain. Understanding how the barrier is developed and maintained throughout the earlier years of adult life can identify key processes that may have beneficial applications in the restoration of the aged brain. With an unprecedented increasing global aged population, the prevention and treatment of age-associated disorders has become a rising healthcare priority demanding novel approaches for the development of therapeutic strategies. The aging cardiovascular system has long been recognised to be a major factor in age-associated diseases such as stroke, atherosclerosis and cardiac arrest. Changes in the highly specialised cerebral vasculature may similarly drive neurodegenerative and neuropsychiatric disease.